EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PUZZLE DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PERBANDINGAN PECAHAN SISWA SEKOLAH DASAR - Esti Yuliani; Aliya Nauli Hidayat; Herlin Anggun Afrilia; Sri Mega Lestari; Hafiziani Eka Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of innovative learning models in education encourages the use of approaches capable of enhancing students' active engagement and problem-solving skills. Fraction comparison material is abstract in nature, thus requiring learning models and media that can help students visualize concepts concretely and contextually through Problem Based Learning assisted by Puzzle media. This study aims to determine the effectiveness of implementing the Problem Based Learning (PBL) model assisted by Puzzle media on students' mathematical problem-solving abilities in fraction comparison material. The study was conducted at one of the public elementary schools in Purwakarta with 25 fifth-grade students of class V-A as subjects, using a Pre-experimental One Group Pretest-Posttest Design. Data were collected through written essay tests consisting of 5 questions administered as pretest and posttest to measure students' ability to analyze (C4) and create (C6). The treatment applied the PBL model through five stages: orienting students to the problem, organizing students for learning, guiding investigation, developing and presenting work, and evaluating the problem-solving process, integrated with Puzzle media as a concrete learning tool. The results showed an increase in the average score from 51.68 on the pretest to 76.96 on the posttest with a difference of 25.28. The Shapiro-Wilk normality test indicated that the posttest data was not normally distributed, leading to the non-parametric Wilcoxon Signed Rank Test. The Wilcoxon test results showed that all 25 students had higher posttest scores than pretest scores (Positive Ranks = 25, Negative Ranks = 0, Ties = 0), with Z = -4.378 and significance p < 0.001, indicating a significant difference between pre- and post-treatment results. The average N-Gain Score of 0.4830 falls in the moderate category, indicating that the Problem Based Learning model assisted by Puzzle media is effective in improving students' mathematical problem-solving abilities in fraction comparison material at the elementary school level.